2022
DOI: 10.1002/htj.22683
|View full text |Cite
|
Sign up to set email alerts
|

A numerical investigation of the effect of sinusoidal temperature on mixed convection flow in a cavity filled with a nanofluid with moving vertical walls

Abstract: The aim of this study is to investigate numerically the effect of sinusoidal temperature on mixed convection flow in a cavity filled with nanofluid and moving vertical walls by using a new temperature function, where thermal heating takes the form of the sinusoidal temperature; and could be found in various natural processes and industries such as solar energy, and cooling of electronic components. The heating is concentrated in the center and then distributed to both ends at different values of Rayleigh numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Many researchers have researched the effects of various parameters in their work, including the Ra number, Volume percentage of nanofluid, and Ri number. From their findings, it has been found that the Ra number and Ri number have considerable value in the Nu number [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have researched the effects of various parameters in their work, including the Ra number, Volume percentage of nanofluid, and Ri number. From their findings, it has been found that the Ra number and Ri number have considerable value in the Nu number [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we dealt with the issue of enhancing heat exchange inside the cavity using the hybrid nanofluid. In this regard, we find many scientific studies carried out by researchers using several methods to improve heat exchange, including Saleh et al 1 studied the effect of the sinusoidal temperature inside a cavity filled with nanofluids. From the obtained result, the increasing Rayleigh number led to a decrease in the boundary layer.…”
Section: Introductionmentioning
confidence: 99%